ANALISIS TERHADAP PUTUSAN MA NO.482K/TUN/2021 TERKAIT SURAT KEPUTUSAN GUBERNUR JAWA TENGAH NO.590/20TAHUN 2021 - Boediningsih, Widyawati; Tandiono, Sudargo (Faculty of Law, University of Dr. Soetomo, 2022)
Mining and the construction of public facilities of course require land acquisition before carrying out activities. However, conflicts of interest or legal issues are often encountered, both from the public who do not agree or there are discrepancies in the decrees issued by the government, both regional and central. Although the dispute can be resolved by filing a lawsuit in the State Administrative Court. However, there is still dissatisfaction from the aggrieved parties so that this research will assist in analyzing the Supreme Court Decision Number 482 K/TUN/2021 related to the dispute over the construction of the Bener dam in Wadas Village, Purworejo, Central Java. Keywords: IUP, Mining, Supreme Court Decision, Andesite